2009
DOI: 10.2176/nmc.49.611
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Recurrence of Granulocytic Sarcoma -Two Case Reports-

Abstract: Two patients presented with rare isolated recurrence of granulocytic sarcoma. A 29-year-old male presented with an extra-and intracranial mass 10 years after bone marrow transplantation for chronic myeloid leukemia. A 34-year-old female presented with an intracranial mass 3 years after complete remission of acute myeloid leukemia-M2a. Both patients underwent surgical resection. The first patient received adequate postoperative radiotherapy and chemotherapy, and achieved complete remission without evidence of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…9,12) Unusual manifestations of extraand intracranial locations of MS have been reported. 9,17,18) In our case, we speculate that the marrow space of the petrous bone was first involved by leukemic cells, then tumor mass developed and extended to the mastoid cavity and intracranial space. MS has been described in association with various chromosomal abnormalities such as t(8;21)(q22;22) translocations, mixed lineage leukemia rearrangements, trisomy 8, and inversion 16.…”
Section: Discussionmentioning
confidence: 65%
“…9,12) Unusual manifestations of extraand intracranial locations of MS have been reported. 9,17,18) In our case, we speculate that the marrow space of the petrous bone was first involved by leukemic cells, then tumor mass developed and extended to the mastoid cavity and intracranial space. MS has been described in association with various chromosomal abnormalities such as t(8;21)(q22;22) translocations, mixed lineage leukemia rearrangements, trisomy 8, and inversion 16.…”
Section: Discussionmentioning
confidence: 65%
“…In some cases involving a large mass or multiple lesions, long-term survival was achieved by performing the transplant with the patient in a non-CR state; however, these lesions make accurate evaluation of the extent of any residual disease remaining after chemotherapy difficult (7)(8)(9). On the other hand, some case reports demonstrated that MS relapsed after allo-HCT for leukemia (12,13). Xu et al reported the case of a patient who presented with extra-and intracranial MS after undergoing a transplant for chronic myelogenous leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al reported the case of a patient who presented with extra-and intracranial MS after undergoing a transplant for chronic myelogenous leukemia. The patient was successfully treated with surgical resection and postoperative radiotherapy and chemotherapy (12). Kai et al reported the case of a patient with acute promyelocytic leukemia who suffered serial extramedullary MS relapses after undergoing allogeneic peripheral blood stem cell transplantation (allo-PBSCT).…”
Section: Discussionmentioning
confidence: 99%